Influence of substrate and pH on the diversity of the aeroterrestrial alga Klebsormidium (Klebsormidiales, Streptophyta): a potentially important factor for sympatric speciation - Ryšánek, David; Holzinger, Andreas; Škaloud, Pavel (Phycologia, 2016)
Our knowledge of the processes involved in speciation of microalgae remains highly limited. In the present study, we investigated a potential role of ecological speciation processes in diversification of the filamentous green alga Klebsormidium. We examined 12 strains representing four different genotypes. The strains were collected from sandstone and limestone rocks and were cultivated at five different pH levels ranging from pH 4 to pH 8. We determined the responses of the 12 strains to the experimental pH conditions by (1) measuring the effective quantum yield of photosystem II, and (2) determining the growth rates after cultivation at different pH levels. Strong differences were found between the results obtained by these two methods. Direct counting of cells revealed a strong ecological differentiation of strains of Klebsormidium isolated from different substrate types. Strains isolated from limestone showed the highest growth rates at higher pH levels; whereas, the strains isolated from sandstone exhibited two distinct growth responses with optima at pH 5 and 6, respectively. In contrast, the effective quantum yield of photosystem II was always down-regulated at lower pH values, probably due to dissolved inorganic carbon limitation. In general, we determined distinct ecophysiological differentiation among distantly and closely related lineages, thereby corroborating our hypothesis that the sympatric speciation of terrestrial algae is driven by ecological divergence. We clearly showed that pH is a critical ecological factor that influences the diversity of autotrophic protists in terrestrial habitats.
Keywords: Speciation; Diversity; Klebsormidium; Protist; pH